Recent Advances in Plasmonic Nanostructures for Enhanced Photocatalysis and Electrocatalysis - Li, Siwei; Miao, Peng; Zhang, Yuanyuan; Wu, Jie; Zhang, Bin; Du, Yunchen; Han, Xijiang; Sun, Jianmin; Xu, Ping (Advanced materials (Weinheim), 2021)
Plasmonic nanomaterials coupled with catalytically active surfaces can provide unique opportunities for various catalysis applications, where surface plasmons produced upon proper light excitation can be adopted to drive and/or facilitate various chemical reactions. A brief introduction to the localized surface plasmon resonance and recent design and fabrication of highly efficient plasmonic nanostructures, including plasmonic metal nanostructures and metal/semiconductor heterostructures is given. Taking advantage of these plasmonic nanostructures, the following highlights summarize recent advances in plasmon‐driven photochemical reactions (coupling reactions, O2 dissociation and oxidation reactions, H2 dissociation and hydrogenation reactions, N2 fixation and NH3 decomposition, and CO2 reduction) and plasmon‐enhanced electrocatalytic reactions (hydrogen evolution reaction, oxygen reduction reaction, oxygen evolution reaction, alcohol oxidation reaction, and CO2 reduction). Theoretical and experimental approaches for understanding the underlying mechanism of surface plasmon are discussed. A proper discussion and perspective of the remaining challenges and future opportunities for plasmonic nanomaterials and plasmon‐related chemistry in the field of energy conversion and storage is given in conclusion. The recent advances in applying the surface plasmon resonance effect from plasmonic nanostructures for enhanced photocatalysis and electrocatalysis are comprehensively summarized, highlighting the synthesis strategies of plasmonic nanomaterials along with future directions of plasmon‐related research.